TELAAH EDISI NASKAH "SADJARAH BANTEN" SEBAGAI SUMBER DATA TEKSTUAL BAGI PENGKAJIAN SEJARAH: Tinjauan Disertasi Titik Pudjiastuti - Wahyudi, Deny Yudo (Jurnal Sejarah dan Budaya, 2010)
Abstract: Manuscript as a traditional historiography resource was a thing of interest on historical process studies. SadjarahBanten as an old document was essential for historical studies and historical inscription in Nusantara. TitikPudjiastutihas written SadjarahBanten manuscriptturn into textual resources on her dissertation could help other knowledge and science, especially on history have got huge information and interpretation on it.